2021
DOI: 10.15388/infedu.2021.17
|View full text |Cite
|
Sign up to set email alerts
|

Educating Students in Technology Enhanced Learning Design by Interweaving Instruction and Assessment

Abstract: Developing an engaging and positive learning environment for learners, especially in a particular course, is one of the most creative aspects of teaching. Learning design supports the design of interventions, which are pedagogically informed, promote student-centered learning activities and make effective use of appropriate resources and technologies. In the context of this work, a framework is proposed for teaching learning design issues in tertiary education which interweaves teacher-centered activities with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…At the level of teaching practice ability, it was found that professional knowledge, professional ability, teaching design, teaching practice, and teaching evaluation were all important, which is similar to previous studies that students in the IPEM should have a solid grasp of professional knowledge, be able to use disciplinary knowledge to solve problems, develop the curriculum design according to the discipline theory, undertake teaching practice, conduct multiple evaluations (Gogoulou & Grigoriadou, 2022), and develop a curriculum that contains reasonable scientific content and a teaching plan that corresponds with the actual situation of college students (Fang, 2019;Mavis Sevim, 2021;Karatas & Yilmaz, 2021). In terms of comprehensive education ability, the experts pointed out that students in the IPEM should have the ability to educate people through courses, activities, and processes (Ai et al, 2019;Liu, 2020;Forster, 2012).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…At the level of teaching practice ability, it was found that professional knowledge, professional ability, teaching design, teaching practice, and teaching evaluation were all important, which is similar to previous studies that students in the IPEM should have a solid grasp of professional knowledge, be able to use disciplinary knowledge to solve problems, develop the curriculum design according to the discipline theory, undertake teaching practice, conduct multiple evaluations (Gogoulou & Grigoriadou, 2022), and develop a curriculum that contains reasonable scientific content and a teaching plan that corresponds with the actual situation of college students (Fang, 2019;Mavis Sevim, 2021;Karatas & Yilmaz, 2021). In terms of comprehensive education ability, the experts pointed out that students in the IPEM should have the ability to educate people through courses, activities, and processes (Ai et al, 2019;Liu, 2020;Forster, 2012).…”
Section: Discussionsupporting
confidence: 80%
“…In terms of teaching practice ability, this was ranked as the most important by the AHP, who indicated that the teaching practice ability of ideological and political educators plays an important role in career development. This means that students in the IPEM should have the professional knowledge and ability to design, practice and evaluate teaching, which was also found in the research of Fang (2019), Gogoulou and Grigoriadou (2022) and Mavis Sevim (2021). As for comprehensive education ability, the result was consistent with that of ideological and political education speciality in line with developing the times and social needs, analysing people's actual confusion in life, using scientific theoretical knowledge to effectively eliminate ideological confusion and obstacles, and promoting effective development and construction (Ai et al, 2019;Ocampo, 2021).…”
Section: Discussionmentioning
confidence: 71%
“…Other qualities include accessibility (Spridzāns, 2023), flexibility, and interactivity (Smith et al, 2021). A technology-enhanced learning environment is positive when it provides constructive feedback (Gogoulou & Grigoriadou, 2021). Besides, the environment should be supportive and adaptable (Rehman, 2023).…”
Section: Creation and Development Of Technology-enhanced Learningmentioning
confidence: 99%
“…Meanwhile, there are other studies emphasized that attitudes towards technology use alone does not influence students' academic performance. These studies reported that other factors such as teaching strategies and learning resources contributes more towards students' academic achievement in TEL environment ( [14]; [21]). It is important to highlight that most of the studies discussing the students' academic achievement generally, very limited studies have explored the relationship between attitudes towards technology and promotion of HOTS in mathematics classroom specifically.…”
Section: Introductionmentioning
confidence: 99%